Influence of Concentration of Graphene Oxide to Thermal Diffusivity in Nano-liquid Form Using Thermal Lens Method - MON, TING LEE; Sa'at, Nor Kamilah; Azis, Raba'ah Syahidah; Mamat, Md Shuhazlly; Ismail, Nur Quratul Aini (Indonesian Journal of Physics, 2024)
This study examines the effect of graphene oxide (GO) concentration on thermal diffusivity in nano-liquid formulations using the thermal lens method. Nano-liquid samples with varied GO concentrations were prepared and analyzed. Results indicate an increase in thermal diffusivity with rising GO concentration up to a threshold, beyond which further increments yield diminishing returns. This behavior is attributed to the unique thermal transport mechanisms enabled by GO nanosheets. These findings offer insights for optimizing GO-based nano-liquids for thermal management applications. Moreover, the study underscores the efficacy of the thermal lens method for probing thermal properties in nanofluid systems.